HEALTH PROFILES OF OLDER NURSING HOME RESIDENTS BY SUICIDAL IDEATION: A LATENT CLASS ANALYSIS. (20th December 2022) - Yuan, Yiyang; Barooah, Adrita; Mack, Deborah; Lapane, Kate; Ulbricht, Christine
Abstract: In US nursing homes, 2% of residents have documentation of suicidal ideation (SI). Whether older residents' health profiles differ by SI is unknown. Using the 9th Patient Health Questionnaire-9 (PHQ-9) item on Minimum Data Set 3.0, we identified 15, 277 older residents with and 562, 184 without SI. Latent class analysis using frailty, cognitive impairment, palliative care index, pain, and remaining PHQ-9 items as indicators identified health profiles by at-admission SI and estimated the association between profiles and SI at 90 days. In residents with at-admission SI, four profiles emerged: (1) frail, intact/moderate cognitive impairment, all depressive symptoms (prevalence: 22.8%); (2) frail, moderate/severe pain, depressed mood, sleep problems, fatigue (32.2%); (3) frail, severe cognitive impairment, depressed mood, fatigue, feelings of worthlessness (22.9%); (4) pre-frail, moderate/severe cognitive impairment, depressed mood (22.0%). Compared to the residents in profile 4, those in profile 1 [adjusted OR (aOR): 1.24; 95% Confidence Interval (CI):1.11-1.37] and those in profile 2 [aOR: 1.11; 95% CI: 1.01-1.22] were more likely to continue reporting SI at 90 days. In residents without at-admission SI, three profiles emerged: (1) frail, depressed mood, fatigue (33.9%); (2) frail, severe cognitive impairment (38.1%); (3) prefrail/frail (28.0%). Residents in profile 1 were more [aOR: 2.80; 95% CI: 2.60-3.00] while those in profile 2 were less [aOR: 0.79; 95% CI: 0.71-0.86] likely profile 1 residents to report SI at 90 days. Findings indicate substantial heterogeneity in the health profiles between and within older residents with and without self-reported SI.